ASR, Volume 22, n° 1, 2018 - Full Issue - journal system (African Sociological Review, 2018)
Contents Editorial .....................................................1 General Issues Thinking Otherwise: theorizing the colonial/gender system in Africa Boris Bertolt .........................................2 Research Papers The origins of the feminist movement in Senegal: A social history of the pioneering Yewwu-Yewwi Hawa Kane & Oumar Kane .......................................................18 Vulnerability and Resilience of Female Farmers to Climate Change in Oku, Cameroon Matilda Azon, Clare J. Kelso & Kammila Naidoo ...........................................31 Morphologie du quotidien, souffrance sociale et parcours individuels au Cameroun: la mort de Monique Koumatekel, un problème social ? Jacquineau Azétsop, Christophe Tchawa, & Sylvestre Omgba Essomba .............................................54 The Impact of Gender and Residential Background on Racial Integration: Evidence from a South African University Josephine Morolake Adeagbo ............................................81 Elèves-mères et rationalité de la sexualité et de la maternité à l’Ouest-Cameroun Meli Meli Vivien, Gnintedem Tchoubou Richelle & Yong Lemoumoun Judeon Socrate ..............94 Participants’ evaluation of the land reform programme in Rwanda’s Southern Province Jean de Dieu Dushimimana & Johan Zaaiman ...................................117